Intra-household arrangements and health satisfaction: Evidence from Mexico - Mariano Rojas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper uses a subjective wellbeing approach to study the role of household arrangements on the health satisfaction of an individual. It also studies the impact of household arrangements on health satisfaction across different income groups, by contrasting two main theories of the family: the altruistic/communitarian theory, which emphasizes altruism within the family, implies that the within-the-household allocation of relevant health satisfaction resources leads towards an egalitarian distribution of health satisfaction, and second, the cooperative bargaining theory according to which the family emerges as the cooperative equilibrium outcome from the unilateral interests of each household member. Thus, each household member takes advantage of their bargaining power to attain an equilibrium that favours their personal interests.
Keywords: I10; 330; health; health satisfaction; subjective wellbeing; intra-household arrangements; Mexico; Gesundheitsökonomik; Zufriedenheit; Mexiko